Public health system challenges in the Free State, South Africa: a situation appraisal to inform health system strengthening - B. Malakoane; J. C. Heunis; P. Chikobvu; N. G. Kigozi; W. H. Kruger (BMC, 2020)
Abstract Background Since the advent of democracy, the South African government has been putting charters, policies, strategies and plans in place in an effort to strengthen public health system performance and enhance service delivery. However, public health programme performance and outcomes remained poor while the burden of disease increased. This was also the case in the Free State Province, where major public health system challenges occurred around 2012. Assessment was necessary in order to inform health system strengthening. Methods The study entailed a multi-method situation appraisal utilising information collated in 44 reports generated in 2013 through presentations by unit managers, subdistrict assessments by district clinical specialist teams, and group discussions with district managers, clinic supervisors, primary health care managers and chief executive and clinical officers of hospitals. These data were validated through community and provincial health indabas including non-governmental organisations, councils and academics, as well as unannounced facility visits involving discussions with a wide range of functionaries and patients. The reports were reviewed using the World Health Organization health system building blocks as a priori themes with subsequent identification of emerging subthemes. Data from the different methods employed were triangulated in a causal loop diagram showing the complex interactions between the components of an (in) effective health system. Results The major subthemes or challenges that emerged under each a priori theme included: firstly, under the 'service delivery' a priori theme, 'fragmentation of health services' (42 reports); secondly, under the 'health workforce' a priori theme, 'staff shortages' (39 reports); thirdly, under the 'health financing' a priori theme, 'financial/cash-flow problems' (39 reports); fourthly, under the 'leadership and governance' a priori theme, 'risk to patient care' (38 reports); fifthly, under the 'medical products/technologies' a priori theme, 'dysfunctional communication technology' (27 reports); and, sixthly, under the 'information' a priori theme, 'poor information management' (26 reports). Conclusion The major overall public health system challenges reported by stakeholders involved fragmentation of services, staff shortages and financial/cash-flow problems. In order to effect health systems strengthening there was particularly a need to improve integration and address human and financial deficiencies in this setting.